Affinity purification using recombinant PXR as a tool to characterize environmental ligands. Issue 2 (5th January 2012) - Dagnino, Sonia; Bellet, Virginie; Grimaldi, Marina; Riu, Anne; Aït‐Aïssa, Sélim; Cavaillès, Vincent; Fenet, Hélène; Balaguer, Patrick
<x xml:space="preserve">Abstract</x> Many environmental endocrine disrupting compounds act as ligands for nuclear receptors. The human pregnane X receptor (hPXR), for instance, is activated by a variety of environmental ligands such as steroids, pharmaceutical drugs, pesticides, alkylphenols, polychlorinated biphenyls and polybromo diethylethers. Some of us have previously reported the occurrence of hPXR ligands in environmental samples but failed to identify them. The aim of this study was to test whether a PXR‐affinity column, in which recombinant hPXR was immobilized on solid support, could help the purification of these chemicals. Using PXR ligands of different affinity (10 nM < EC50 < 10 μM), we demonstrated that the PXR‐affinity preferentially column captured ligands with medium to high affinities (EC50 < 1 μM). Furthermore, by using the PXR‐affinity column to analyze an environmental sample containing ERα, AhR, AR, and PXR activities, we show that (i) half of the PXR activity of the sample was due to compounds with medium to high affinity for PXR and (ii) PXR shared ligands with ERα, AR, and AhR. These findings demonstrate that the newly developed PXR‐affinity column coupled to reporter cell lines represents a valuable tool for the characterization of the nature of PXR active compounds and should therefore guide and facilitate their further analysis. © 2012 Wiley Periodicals, Inc. Environ Toxicol 29: 207–215, 2014.